Location Patterns And Location Factors In Cultural And Creative Industries - Tomczak, Paulina; Stachowiak, Krzysztof (Quaestiones Geographicae, 2015)
The paper analyses spatial and locational aspects of cultural and creative industries (CCI) taking into consideration the internal heterogeneity of this group of activities. Emphasis is put on similarities and differences in those aspects found for the sector as a whole and for its individual branches. On the basis of the proposed criteria the paper tries to exemplify a set of CCI characteristics, on the one hand to highlight their diversity, and on the other, to select the best criteria for analysing spatial and locational aspects of CCIs. A detailed analysis of CCI location patterns and location factors is also carried out, and on this basis two groups of models of the spatial aspects of CCIs are proposed: those of CCI location and those of the range of CCI markets.